Digital literacy and the national curriculum for England: Learning from how the experts engage with and evaluate online content. (July 2020) - Polizzi, Gianfranco
Abstract: Educationalists' and policymakers' curriculum work on digital literacy in England has overlooked the expertise of digital specialists such as information, IT and media professionals. Given the lack of evidence, this article draws on semi-structured interviews with experts in the United Kingdom, enhanced by a diary methodology and a conversational approach to the think aloud method, to explore how they engage with and evaluate online content. In doing so, it addresses what digital literacy entails and how to promote it across the national curriculum for England. It is argued that the ability to evaluate online content involves not only reflections on the nature and origin of information, contextual knowledge and the use of multiple sources, but also functional and critical digital skills and knowledge about the internet and the digital environment. Relatedly, it is argued that the Citizenship and Computing curricula should be revised to promote digital literacy as a cross-curricular subject. Highlights: This study explores how digital experts in the UK engage with and evaluate online content. As a result, it reflects on what digital literacy entails and how to promote it across the national curriculum for England. Digital literacy relies on reflections on information, contextual knowledge and the use of multiple sources. In addition, it requires functional and critical digital skills and knowledge. The Citizenship and Computing curricula should be revised to promote digital literacy.